Are Eating Habits Associated with Overweight/Obesity among Indonesian Women Adults? Based on The Indonesian Family Life Survey (IFLS) 5 in 2014 - Sabitha Wina octarine; Trias Mahmudiono (Media Gizi Kesmas, 2022)
Background: Eating habits were often linked with overweight or obesity. Several types of food that are often consumed by the public were known to be associated with the occurrence of being overweight/obesity. But information about the association of each type of food is lacking especially in young adults.   Objectives: This study aimed to analyze the association between eating habits with overweight status among women young adults in Indonesia.   Methods: This study analyzed 4966 adults from the fifth waves of the Indonesian Family Life Survey (IFLS5) in 2014. Eating habits are measured by the frequency of consumption of each type of food. A chi square test and logistic regression were used to explore the association between the variables with the overweight status among women young adults. Results: The prevalence of overweight and non-overweight were known to be 41.1% and 59.9%. Milk; cheese; and others consumption (p=0.006) and rice consumption (p=0.017) had negative correlation with overweight/obesity meanwhile sweet foods consumption was associated with overweigh/obesity (p=0,034). On the other hand, it is shown that there is no association between egg consumption, meat consumption, soft drink consumption, and fast food consumption with overweight status among women young adult (p>0,05). Conclusions: It was concluded that the consumption of sweet foods was associated with a higher likelihood of being overweight or obese. In addition, the consumption of rice and milk; cheese; butter; and others that were less frequent associated with a lower likelihood of being overweight or obese. Therefore, the consumption of sweet foods among adult needs to be limited in order to reduce and prevent the problem of being overweight.